If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 8(x + 5) Reorder the terms: 9x = 8(5 + x) 9x = (5 * 8 + x * 8) 9x = (40 + 8x) Solving 9x = 40 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9x + -8x = 40 + 8x + -8x Combine like terms: 9x + -8x = 1x 1x = 40 + 8x + -8x Combine like terms: 8x + -8x = 0 1x = 40 + 0 1x = 40 Divide each side by '1'. x = 40 Simplifying x = 40
| 3(-x-1)=12 | | -y+2(-3)=10 | | -112+4=2 | | 1x=2x^2-8x+7 | | 1/3x-1=3 | | 25=5/6x | | 4x^2-16=16 | | 3y+3+(2y+7)=9y-14 | | (16b)1/2(6b1/4) | | 7a+7-3a=5+8a-1 | | 160/2=x | | 22x-6-12x+2=26x-4-16x+11 | | T-5=-5t+-25 | | 169/2=x | | 2a+3(a-7)-8=79 | | 12/(8-n)=3 | | -2/(7/8) | | -13-7p=-p-1+6 | | P=140-4Q | | -3x+19=-50 | | F(x)=-14x^2+8.2x+6 | | X-0.50x=13.75 | | 6x-8x+2=3x+6 | | 2/3×55 | | 8-4/5g-1612g | | 7(5x-9)=42 | | 31-[3+6y-3(y+2)]=-2(3y-5)-[7(y-1)-4y+1] | | 4t+11=4t-11 | | 6x-8x+2=4x+6 | | 35=3+5a | | 5-5x=-4x+16 | | 7x^2-5x+14x-10=0 |